Triboelectric Separation - Beneficiation of Coal (The Australasian Institute of Mining and Metallurgy, 2010)
Triboelectric Separation - Beneficiation of Coal The performance of triboelectric separators is highly sensitive to the selectivity of the particle charging process. This paper presents a quantitative study on triboelectric coal beneficiation. The performance of different charging media was studied. Stainless steel was identified as having a work function between that of coal and silicate gangue and found to be the optimum charging medium for coal beneficiation. Recent results from separation tests were performed where silicate gangue was separated from crude coal using a parallel plate free-fall separator are illustrated.